Relación entre el rendimiento, estrés académico y dimensiones de personalidad en universitarios - Galdós-Tanguis Parodi, Andrea (2014)
The following research presents as main objective to identify the relationship between academic performance, academic stress and the personality dimension of the university students. The results show that higher levels of extraversion, the lower the perceived situations generating academic stress and lower the symptoms presented by the student. No relationship was found between extraversion dimension and academic performance. Moreover, the evidence indicates that higher levels of neuroticism, the greater the perceived situations generating greater academic stress and the symptoms presented by the student. No relationship was found between neuroticism dimension and academic performance. Regarding the findings, it appears that there is a relationship between the personality dimensions of the sample and academic stress. Also, that those dimensions do not influence their academic performance, that is, this could be related to other variables or determinants.